Associations between paternal autism traits and parenting from the Japan environment and children’s study - Aya Sakakihara; Toshio Masumoto; Youichi Kurozawa; The Japan Environment and Children’s Study Group (Scientific Reports, 2024)
Abstract There are few studies on the parenting of fathers with autism traits. To investigate this issue, we examined the type of parenting performed by fathers with autism traits using data from a nationwide birth cohort study, the Japan Environment and Children’s Study. Paternal parenting was evaluated by mothers or caregivers when the child was 2 years old. Father’s autism traits were measured using the Japanese version of the self-administered Autism Spectrum Quotient. Logistic regression analysis was performed to statistically analyze the data. Fathers with autism traits were significantly less likely to prepare meals for their child and helping them eat (adjusted OR (aOR): 1.11, 95% confidence interval (CI): 1.01–1.23), to helping the child change clothes (aOR: 1.17, 95% CI: 1.04–1.31). However, there were no associations between some parenting behaviors and autism traits (not changing diapers, not bathing with the child, and not playing with the child). Father’s communication skill difficulties by autism traits associated with a lower tendency to perform all types of parenting. Interestingly, there were association between difficulties with social skills or attention-switching and more performing change diapers. These results indicate it is important to respect the child-rearing that fathers with autistic tendencies are able to do, while supporting them in child-rearing that they are significantly less able to do than fathers without autistic tendencies.